2012
DOI: 10.1039/c2gc16485j
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid sol–gel double metal cyanide catalysts for the copolymerisation of styrene oxide and CO2

Abstract: Hybrid sol-gel catalysts of zinc hexacyanocobaltate and SiO 2 were prepared by co-precipitation of the double metal cyanide with silica. Hybrid catalysts prepared at moderately acidic conditions showed the best performance with respect to activity, selectivity and stability. The hybrid sol-gel materials displayed high catalytic activity for the copolymerisation of styrene oxide and carbon dioxide (up to 650 mol SO (mol Zn h) −1 ) and high productivity (575 g Polymer g Catalyst −1 ). They also displayed good se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 40 publications
0
36
0
1
Order By: Relevance
“…We demonstrated that the carbonate fraction could be increased up to 64% by employing a dual catalytic system composed of a DMC and a Salen‐cobalt(III) complex . In this work, we report the simple preparation of a new type of DMC catalyst, which exhibits a high CO 2 incorporation (up to 67 mol %) and thus provides a successful derivatization of the conventional DMC catalyst …”
Section: Introductionmentioning
confidence: 95%
“…We demonstrated that the carbonate fraction could be increased up to 64% by employing a dual catalytic system composed of a DMC and a Salen‐cobalt(III) complex . In this work, we report the simple preparation of a new type of DMC catalyst, which exhibits a high CO 2 incorporation (up to 67 mol %) and thus provides a successful derivatization of the conventional DMC catalyst …”
Section: Introductionmentioning
confidence: 95%
“…The conversion of CO 2 into value added chemicals has been widely investigated in an attempt to reduce the atmospheric levels of CO 2 . Recently, CO 2 has attracted great interests as an environmentally benign building block in the chemical industry due to its non-toxic, non-flammable and recyclable properties [1][2][3][4]. However, CO 2 is a very stable compound as the carbon atom is in the most oxidized form and thermodynamically stable [5] and therefore large energy input is required to transform CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…And no obvious decomposition and changes of structure was observed at 200 °C in all samples (Figure S1 and Figure S2). Notably, accounting for the influence of Mn on f CO2 ’ and CU’ value, it was more preferable to evaluate the CO 2 activation ability with f CO2 and the by‐product PC was generated from the back‐biting process of growing chain which also should be taken into account.…”
Section: Resultsmentioning
confidence: 99%